2003
DOI: 10.1136/ip.9.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of effects of a brief intervention on parental restrictions of teen driving privileges

Abstract: Objective: The purpose of this study was to determine the extent to which effects of exposure to a brief intervention designed to increase parental restrictions on teen driving privileges persisted over time. Design: A total of 658 parents and their 16 year old adolescents were recruited from a local motor vehicle administration (MVA) site as adolescents successfully tested for provisional licenses. At the MVA, parents completed written surveys about expected teen driving during the first month of provisional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…65 Various parent-teen agreements have been used to codify restrictions, 22,66,67 to offer an understanding of both teen and parent responsibilities and expectations, and to create a framework whereby restrictions are reduced with increased experience. [21][22][23]68 Perhaps because of the clarity and structure they provide, parent-teen agreements have both short-term and sustained benefits. 21,65 Monitoring may facilitate effective targeted discussions or may be construed as controlling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…65 Various parent-teen agreements have been used to codify restrictions, 22,66,67 to offer an understanding of both teen and parent responsibilities and expectations, and to create a framework whereby restrictions are reduced with increased experience. [21][22][23]68 Perhaps because of the clarity and structure they provide, parent-teen agreements have both short-term and sustained benefits. 21,65 Monitoring may facilitate effective targeted discussions or may be construed as controlling.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23]68 Perhaps because of the clarity and structure they provide, parent-teen agreements have both short-term and sustained benefits. 21,65 Monitoring may facilitate effective targeted discussions or may be construed as controlling. 69 Shope et al 19 found that it was the combination of parental monitoring, nurturing, and family connectedness that decreased crash rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to technological solutions, parents of teenage drivers also play a significant role in their teen's driving safety. They are responsible for enforcing the graduated driver licensing policies and driving restrictions by controlling access to their teen's vehicle (Simons-Morton, Hartos, & Beck, 2003). Even a brief intervention at the time of teen provisional licensure has proven successful in increasing parental restrictions on teen driving privileges (Simons-Morton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They are responsible for enforcing the graduated driver licensing policies and driving restrictions by controlling access to their teen's vehicle (Simons-Morton, Hartos, & Beck, 2003). Even a brief intervention at the time of teen provisional licensure has proven successful in increasing parental restrictions on teen driving privileges (Simons-Morton et al, 2003). By simply showing a short video on the risks of teen driving and providing both parents and teens with a driving agreement listing teen driving risks and suggestions for families on setting driving rules for teens, Simons-Morton and colleagues (2003) reported significant treatment group differences that were still present nine months later.…”
Section: Introductionmentioning
confidence: 99%